Digital viticulture: Grape farming with smart technologies - Yadav, Deependra Singh; Kaushik Banerjee (Indian Horticulture, 2025)
Digital viticulture integrates advanced digital tools like AI, IoT, and data analytics into grape farming to optimize production, minimize environmental impact, and enhance crop quality. Key components such as IoT sensors, drone and satellite imagery, and data-driven decision support systems enable real-time monitoring and efficient management of vineyards. These innovations help address significant challenges in Indian viticulture, including water scarcity, pest and disease pressures, climate variability, labour shortages, and inconsistent market prices. Globally, countries like Spain, France, and the U.S. have advanced digital viticulture through innovations in robotics, UAVs, and precision management systems. In India, initiatives by ICAR-NRCG and partnerships with universities have begun exploring intelligent viticulture, emphasizing water-efficient irrigation, automated advisories, and stress detection in vineyards. Despite the potential of digital viticulture, challenges such as high initial costs, technical expertise gaps, datamanagement, and privacy concerns need to be addressed for widespread adoption. Enhanced infrastructure, farmer training, and localized technology solutions are essential to realizing the full benefits of digital viticulture in India.